Evaluación del impacto de una intervención educativa en atención farmacéutica y farmacia clínica - Lucchetta, R. C. [UNESP]; Veiga Capela, M. [UNESP]; Santos, Jean Leandro dos [UNESP]; De Carvalho Mastroianni, P. [UNESP] (My University, 2012)
Introduction: The World Health Organization considers pharmaceutical care (PC) of fundamental importance for the patient and the community. Its exercise requires knowledge and skills, which can be acquired in academic and/or continuing educations, credited for effectiveness and impact evaluation. However, few manuscripts in the literature have showed the contribution of the educational interventions on the knowledge, skill and attitude of students and professionals who participate in scientifi c events related to PC. Objective: To evaluate the impact of an educational intervention (EI), and its degree of satisfaction, to pharmacists and pharmacy students. Method: A quasi-experimental study was performed, through an extension course with 40 hours of lectures approaching issues related to PC and clinical pharmacy (CP). Participants answered a survey which was handed out before and after the EI. The statistic tests of Sinais and Mann-Whitney were applied to evaluate the EI signifi cance. Results: Participants (n= 49) were mostly (n= 34) students and performing activities related to PC and CP (n= 20). Statistics differences, before and after the EI, were found in the scores of knowledge, skill and attitude (p <0.001). The evaluated item which showed the most improvement was the last one. Most (n= 30) had exceeded or met their expectations (n= 19). Conclusions: The analysis of the data led us to conclude that an EI of 40 h/week about knowledge, skill and attitude in PC using traditional methods, improves knowledge and problem-solving skills of participants. ©2012 Ediciones Mayo, S.A. All rights reserved.
Assessment of the impact of educational intervention in pharmaceutical care and clinical pharmacy
Keywords: Continuing education; Educational measurement; Evaluation studies as topic; Pharmaceutical care; Pharmacy education; clinical pharmacy; human; knowledge; major clinical study; medical education; pharmaceutical care; pharmacist; pharmacy student; problem solving; professionalism; quasi experimental study; satisfaction; skill; student attitude; world health organization